PENGARUH KOMPENSASI TERHADAP DISIPLIN KERJA KARYAWAN CV JAYA MITRA ABADI PEKANBARU - Putra, Eka (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This research was conducted at CV JAYA MITRA ABADI PEKANBARU. The population in this study were employees of CV Jaya Mitra Abadi Pekanbaru, totaling 33 people. Saturated sampling is a sampling technique when all members of the population are used as samples. In this study the number of samples as many as 32 employees other than the author. The results of this research hypothesis are t arithmetic 4.117 > t table 2.042 and also significance 0.000 <0.05. So the decision is that compensation has a significant effect on employee work discipline at CV Jaya Mitra Abadi Pekanbaru